Efficiency of lachrymal sac drainage in newborns with dacryocystocele. - V. N. Sakovich; V. N. Serdyuk; N. G. Klopotskaya; I. N. Tarnopol'skaya (Medičnì Perspektivi)
The article represents results of treatment of 14 newborns with unilateral dacryocystocele. Patients age was 7.2±0.5 days. In 9 newborns (64.3%) dacryocystocele was complicated with lachrymal sac phlegmon; in 5 children (35.7%) any complications were absent. Drainage of lachrymal sac through the lower lachrymal canaliculus, instillation of antibiotics, systemic antibiotic therapy in case of phlegmon were performed in all the children. Lachrymal sac washing was performed with a solution of the antibiotic ofloxacin till clear fluid evacuation. If necessary the drainage was repeated in 10 days. The drainage of lachrymal sac was successful in all the patients. 2-3 weeks after the drainage probing of nasolachrymal duct was perfomed in 4 children (28.6%) including those 3 with lacrymal sac phlegmon. In 71.4% regression of dacryocystocele occurred itself. Any complications and side effects were not observed. Positive effect of the drainage, according to the authors, can be explained so that dilatation of lachrymal canaliculus before the procedure allows to eliminate Rosenmüller valve stenosis and  evacuation of fluid, mucus and pus, being breeding ground for microorganisms from lachrymal sac, promotes inflammation subsiding. Authors also recommend to pay attention on prenatal diagnosis of dacryocystocele, using ultrasound investigation in the 3rd trimester of pregnancy.